Introduction to the “Circum-Arctic Palynological Event Stratigraphy” (CAPE) series of papers - Bujak, Jonathan; Fensome, Robert; Mangerud, Gunn; Williams, Graham (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2021)
Palynomorphs are one of the few groups of fossils that provide biostratigraphic control in marine to nonmarine rocks and can be applied as proxies for paleoenvironmental and paleoclimatic interpretations. Their utility is enhanced by their microscopic size, which is usually less than 200 micrometres; they are thus easily recovered from small rock samples. They occur throughout the Phanerozoic and are therefore invaluable in refining biostratigraphic control of Arctic successions in Alaska, Arctic Canada, Greenland, northern Europe, and northern Russia. The objective of the Circum-Arctic Palynological Event (CAPE) Stratigraphy series of papers is to integrate data published on Arctic palynomorphs to delineate palynological events (palynoevents) across the Arctic for the Silurian to Cenozoic. Once the series of papers is complete, the data will also be used to compile a TimeScale Creator datapack that can be updated and calibrated on an ongoing basis. Palynoevents include taxon originations (first occurrences or FOs) and extinctions (last occurrences, or LOs) and some abundance events. The palynoevents are correlated with established chronostratigraphic horizons such as bases of ammonoid zones or stages, and hence their chronostratigraphy is independent of the absolute time scale in millions of years. In addition to the palynostratigraphic papers, the series includes a paper detailing the paleogeography of the circum-Arctic regions, including informative maps, as well as a paper providing a palynological perspective of the Cenozoic shift from greenhouse to icehouse conditions.